DEVELOPMENT OF SHU CALCULATION AND DEVELOPMENT SYSTEMS (REMAIN BUSINESS RESULTS) ON EMPLOYEE COOPERATIVES “PERDANA ASIA” PT. BANK CENTRAL ASIA, TBK - Onne Sesaphing; Anita Wijayanti; Riana Rachmawati Dewi (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2019)
The purpose of this study is to find out the system of calculation and distribution of SHU (Remaining Business Results) on employee cooperatives "Regional Regulation of Asia" and then develop a system of calculation and distribution of the remaining operating results that are correct and in accordance with the standard calculation of the remaining results of savings and loan cooperatives. this is research and development (R & D) research, where the research subject is the Prime Asia Employee Cooperative and the object of research is a system of calculation and division of the remaining results of the business. The method of data collection consists of interviews and observations. The analytical method used is data reduction by analyzing the existing system then the presentation of data in the form of a comparison of systems that are being used with the development of the system that will be used which will then provide results that are appropriate to the requirements and in accordance with applicable standards. and the distribution of the remaining proceeds to the cooperative of the Asian prime employees, the SHU funds received by members are more accurate because all the data has been confirmed correctly and the calculation has been adjusted to the standard calculation of the remaining savings and loan cooperatives.